Effects of a Blueseventy™ bodysuit on spatial-temporal and coordinative parameters during an all-out 50-m front crawl stroke - Silveira, R. P.; Kanefuku, J. Y.; More, F. C.; Castro, F. A. S (Biomechanics and Medicine in Swimming XI, 2010)
The aim of this study was to establish the effects of using a shoulder to ankle bodysuit (BlueseventyTM) on spatial-temporal and coordinative parameters during an all-out 50m front crawl swim. Six subjects (16.6 ± 2.0 yrs) performed two all-out 50m trials (with and without bodysuit). The arm stroke parameters and index of coordination were determined by videography. A repeated measures ANOVA was performed, with main effects verified using LSD post-hoc for an á < 5 %. Using the bodysuit, swimming speed and stroke length were higher. The duration of the entry and catch phase and non-propulsive phase were shorter in the second 25 m split. No statistical differences in index of coordination were found. Wearing the bodysuit significantly improves the swimming performance, mostly on the second half of the test.